Livelihood Diversification Strategies: Resisting Vulnerability in Egypt - Imane Helmy (Global Labor Organization (GLO), 2020)
Livelihood diversification is attracting considerable interest as a tool to cope with economic shocks and resist vulnerability. This paper investigates the evolution of livelihood diversification in Egypt with a particular focus on wealth and urban-rural divides. Using Egypt Labor Market Panel data from 2006 to 2018, I find that rural households have a more diversified livelihood portfolio, yet they diversified away from farming over time. Poor rural households remained dependent on informal livelihood strategies due to the high entry barriers to formal employment. Urban households had significantly less livelihood diversification than rural households. Wealthy households in urban areas tended to depend on relatively more specialized livelihood clusters which were stable over time. These findings imply that distress is a potential reason for diversification in urban areas.
Keywords: O10; D1; D60; 330; livelihood; diversification strategies; vulnerability; informality; Egypt